TRANSLATING LEXICAL COLLOCATIONS IN JOURNALISTIC TEXTS: THE CASE OF ENGLISH AND MACEDONIAN (Journal of Contemporary Philology, 2019)
Collocations play a vital role in language by making it sound more natural, precise and interesting. Hence, handling collocations with special care and vigilance should be high on translators’ agendas. The aim of this study was to determine how Macedonian translators fare in rendering lexical collocations from Macedonian into English in journalistic texts. The questions addressed were the following: Are lexical collocations correctly rendered from Macedonian into English?; Are the same types of lexical collocations preserved in the translated texts?; What are the high-frequency and the low-frequency lexical collocations in the original and translated texts?; What translation strategies are employed in rendering lexical collocations? The results of the study indicate that there is a high level of awareness on the part of translators when it comes to rendering collocations correctly. Surprisingly, there were also more similarities than differences in the internal structure of TL and SL lexical collocations, with the most prominent types in both languages being: adjective + noun and verb + noun. Finally, literal translation was the most frequently employed translation strategy, yielding mostly positive results in all likelihood because all of the analysed collocations were used in the domain of politics and were cross-linguistic.
Keywords: lexical collocations; news articles; translation strategies